2010
DOI: 10.1177/1533317510375083
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Ceruloplasmin Abnormalities in Alzheimer’s Disease

Abstract: The idea that copper may play a role in the pathogenesis of Alzheimer's disease is gaining momentum. Serum copper and ceruloplasmin were measured by both enzymatic (eCp) and immunologic (iCp) methods in 28 patients with Alzheimer's disease and 29 age-matched controls. ''Free copper'' was determined by subtracting copper accounted for in the eCp assay from total serum copper. Percentage free copper, that is the proportion of serum copper not bound to ceruloplasmin, was significantly elevated in patients with Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 25 publications
4
55
1
1
Order By: Relevance
“…No difference in CP concentration was found between the AD patients and the controls, but CP activity and specific activity (activity divided by mass) was significantly lower in the AD patients. In the study by Snaedal et al [9], CP concentration was normal but CP activity was decreased in AD patients compared with controls, which is in agreement with our results and further supported by the results of Brewer et al [13] published in 2010, who found no difference in CP concentration between AD patients and controls, but circulating CP without oxidative activity was increased in AD patients. On the other hand, in a study by Squitti et al [14], CP concentration was raised in the serum of AD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No difference in CP concentration was found between the AD patients and the controls, but CP activity and specific activity (activity divided by mass) was significantly lower in the AD patients. In the study by Snaedal et al [9], CP concentration was normal but CP activity was decreased in AD patients compared with controls, which is in agreement with our results and further supported by the results of Brewer et al [13] published in 2010, who found no difference in CP concentration between AD patients and controls, but circulating CP without oxidative activity was increased in AD patients. On the other hand, in a study by Squitti et al [14], CP concentration was raised in the serum of AD patients.…”
Section: Discussionsupporting
confidence: 93%
“…It seems that the patients in the present study (table 1), the study by Brewer et al [13] and the patients with CSF-confirmed AD in the study by Kessler et al [16] are older and/or with more progressive AD than the patients in the study by Squitti et al [15] (2008). This may explain the discrepancy between the results of these studies and raises the question of whether early changes in CP are present in younger individuals who will later develop AD.…”
Section: Discussionmentioning
confidence: 49%
“…Given that CSF ferroxidase activity is substantially due to Cp (Madsen and Gitlin, 2007), it is reasonable to associate the Cp oxidative modifications found in PD patients with the reported reduction in CSF ferroxidase activity (Boll et al, 1999(Boll et al, , 2008. Furthermore, oxidative modification in Cp leads to copper release (Kang et al, 2001; this study), a finding that possibly explains why copper increases in the CSF of both PD and AD patients (Boll et al, 2008;Brewer et al, 2010). Copper ions released from oxidized Cp facilitate Fenton's reaction, which amplifies general protein damage (Kang et al, 2002).…”
Section: Discussionmentioning
confidence: 61%
“…Besides, emerging in vitro evidence have demonstrated that Cp may enhance the oxidation of DNA [50] and LDL, both by intact Cp [51] and after release of redox-active copper by low pH [52]. The aforementioned factors influencing the antioxidant properties of Cp may account for the lack of association regarding this marker, and for the discrepancies with the other few small studies on this topic [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this thesis has not been definitely confirmed by solid epidemiological data, mainly because of important methodological limitations (i.e., small sample size, lack of consideration of important confounding factors, etc.) affecting the available current literature [25][26][27][28][29][30]. In the attempt to shed light upon this still confusing and uncertain scenario, we conducted the present study dealing with the evaluation of serum paraoxonase, arylesterse, and FeOXs activity in a large sample of older individuals (n = 593) including patients affected by VAD, LOAD, mild cognitive impairment (MCI), and cognitively healthy controls.…”
Section: Introductionmentioning
confidence: 99%